1999
DOI: 10.1016/s0092-8674(00)80722-9
|View full text |Cite
|
Sign up to set email alerts
|

A Primer on Vesicle Budding

Abstract: Do cargo proteins influence this process? Recent work * Department of Molecular and Cell Biology and on the exchange of proteins between the endoplasmic † Howard Hughes Medical Institute reticulum (ER) and the Golgi apparatus in Saccharo-University of California myces cerevisiae and higher eukaryotes suggests that Berkeley, California 94720 all three requirements for functional vesicle budding could be regulated in a single mechanistic step, the formation of a "priming complex" of a small GTPase, a Transport v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
202
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 265 publications
(215 citation statements)
references
References 18 publications
6
202
0
4
Order By: Relevance
“…The cargo molecules are recruited into a newly forming carrier vesicle by cytoplasmic coat molecules (Matsuoka et al, 1998;Bremser et al, 1999). The recruitment of two of the known coats, COPI and COPII, is regulated by small ARF-like GTPases and appears to be a relatively simple process (Lowe and Kreis, 1998;Springer et al, 1999). COPII coat recruitment also is regulated by phosphorylation, since serines of the sec31p component of the COPII coat need to be phosphorylated for full coating activity (Salama et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The cargo molecules are recruited into a newly forming carrier vesicle by cytoplasmic coat molecules (Matsuoka et al, 1998;Bremser et al, 1999). The recruitment of two of the known coats, COPI and COPII, is regulated by small ARF-like GTPases and appears to be a relatively simple process (Lowe and Kreis, 1998;Springer et al, 1999). COPII coat recruitment also is regulated by phosphorylation, since serines of the sec31p component of the COPII coat need to be phosphorylated for full coating activity (Salama et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the transient interaction Glo3p with the v-SNAREs Sec22p and Bet1p renders the SNAREs more protease resistant (Rein et al, 2002). This conformational change may promote the inclusion of SNAREs into vesicles, and they might even serve as primers for vesicle formation (Springer et al, 1999;Spang, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Arf1p is activated through interaction with an ARF guanine nucleotide exchange factor (ArfGEF) at the membrane (Donaldson and Jackson, 2000). Subsequently, coatomer is recruited and forms a complex with Arf1p, cargo, or soluble N-ethylmaleimidesensitive factor attachment protein receptor (SNARE) and an ARF-GTPase activating protein (ArfGAP), a so-called primer (Springer et al, 1999;Spang, 2002). This interaction does not require the deactivation of Arf1p by a GAP.…”
Section: Introductionmentioning
confidence: 99%
“…Tom Yeung, unétudiant du labo, a montré, par le test d'incorporation d'une protéine SNARE, que les membranes isoléesà partir de cellules traitéesà la cycloheximide, par conséquent purgées des protéines nouvellement synthétisées,étaient parfaitement actives pour bourgeonner en vésiculesà COPII (Yeung et al, 1995). Bien que le cargo biosynthétique ne soit pas forcément essentiel au bourgeonnement vésiculaire, nous avons suggéré que les protéines qui cyclent entre le RE et le Golgi pourraient constituer unélément essentiel de la contribution membranaireà la formation d'un bourgeon COPII (Springer et al, 1999).…”
Section: Copii Est Responsable Du Bourgeonnement Vésiculaireà Partir unclassified